An overlooked cause of retrosternal pain: Tetracycline-induced esophagitis - Tolga Duzenli; Ali Attila Aydin; Harun Aslan (Medicine Science, 2018)
Chest pain is one of the most common admission symptoms of emergency services. The differential diagnosis is usually challenging but also very important for emergency physicians. After the exclusion of cardiac sources; noncardiac etiologies must be evaluated. Herein, we report a remarkable case who referred to our emergency department with chest pain and eventually diagnosed as tetracycline-induced esophagitis. Pill esophagitis should be kept in mind in the differential diagnosis of noncardiac chest pain. [Med-Science 2018; 7(2.000): 451-2]